Disruption of crosstalk between LX-2 and liver cancer stem-like cells from MHCC97H cells by DFOG via inhibiting FOXM1. (21st November 2019) - Chen, A; Xu, Chang; Luo, Yimin; Liu, Lihua; Song, Kun; Deng, Guangqi; Yang, Mengjie; Cao, Jianguo; Yuan, Liming; Li, Xiang
Abstract: Hepatic stellate cell (HSC) line LX-2 is activated by liver cancer stem-like cells (LCSLCs) and produces various cytokines that make up most of the hepatocellular carcinoma (HCC) microenvironment. The new genistein derivative, 7-difluoromethoxyl-5, 4′-di-n-octylgenistein (DFOG), shows anticancer effects in multiple malignancies by controlling forkhead box M1 (FOXM1). In this study, we aimed to assess whether DFOG disrupts the crosstalk between human HSC LX-2 cells and LCSLCs. Distinct generations of MHCC97H-derived spheres were obtained with the second generation considered as LCSLCs which displayed enhanced self-renewal ability and elevated expression levels of CD133, CD44, and EpCAM proteins, as well as tumorigenicity, as revealed by colony formation assay in vitro and tumorigenicity assay in vivo. LX-2 and MHCC97H cells were co-cultured with/without DFOG (1, 5, and 10 μM, respectively) using the transwell system. FOXM1 overexpression and/or knockdown were employed for mechanistic investigations. Our results suggested that Co-CM promoted LX-2 cell transformation into liver cancer-associated HSCs. Meanwhile, FOXM1 was up-regulated and the level of hepatocyte growth factor (HGF) was increased in LX-2 cells and in the supernatant after Co-CM stimulation. Sphere and colony formation abilities in MHCC97H cells, and protein levels of CD133, CD44, and EpCAM, were also markedly elevated. DFOG dose-dependently inhibited the above effects, similar to FOXM1 knockdown in LX-2 cells. FOXM1 overexpression reversed the inhibitory effects of DFOG or FOXM1 knockdown or both on LX-2 cell activation and LCSLC feature induction in MHCC97H cells by LCSLC/LX-2 co-culture. This study demonstrated that DFOG disrupts the crosstalk between HSCs and LCSLCs to suppress LCSLC features via down-regulating FOXM1 expression and reducing HGF secretion in HSCs.